2020
DOI: 10.1159/000511822
|View full text |Cite
|
Sign up to set email alerts
|

Diverticular Disease of the Appendix Is Associated with Complicated Appendicitis

Abstract: <b><i>Introduction:</i></b> Diverticular disease of the vermiform appendix (DDA) has an incidence of 0.004 to 2.1% in appendicectomy specimens. DDA is variably associated with perforation and malignancy. We report a single-center experience of DDA. The primary aim is to validate the association of DDA with complicated appendicitis or malignancy, and the secondary aim is to validate systemic inflammatory response syndrome (SIRS) criteria and quick Sepsis-related Organ Failure Assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…One of the differential diagnoses in the present case was mucinous carcinoma arising from the appendiceal diverticulum. Although there are reports that diverticular disease of the appendix may be associated with malignancy, a recent paper suggested that diverticular disease of the appendix is not associated with malignancy (9). In the present case, immunohistochemistry of the cut tumor surface confirmed the presence of another digestive lumen structure surrounding the tumor in addition to the initial colonic lumen structure.…”
Section: Discussionsupporting
confidence: 51%
“…One of the differential diagnoses in the present case was mucinous carcinoma arising from the appendiceal diverticulum. Although there are reports that diverticular disease of the appendix may be associated with malignancy, a recent paper suggested that diverticular disease of the appendix is not associated with malignancy (9). In the present case, immunohistochemistry of the cut tumor surface confirmed the presence of another digestive lumen structure surrounding the tumor in addition to the initial colonic lumen structure.…”
Section: Discussionsupporting
confidence: 51%
“…The congenital type is rare and accounts for 3% of all diagnosed appendix diverticulosis cases [9][10][11]. Appendiceal diverticulitis risk factors are male gender, age over 30, cystic fibrosis, and Hirschsprung disease [12]. Appendiceal diverticulitis is not only a rare condition that can mimic other diseases' symptoms, and most of all, it is confused with acute appendicitis, but also it can be synchronous with other serious diseases such as carcinoid tumors [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Still, both methods are highly dependent on radiologists' experiences [10,13]. On the other hand, the diagnosis of appendiceal diverticulitis may not be possible due to the small size or involvement of inflammatory mass [12]. So, the definitive diagnosis way is a postoperative pathology report [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study including 125 patients, Nozoe et al [ 27 ] reported that the SIRS score was lower in patients who were recommended non-operative management (NOM)[ 27 ]. Similarly, diverticular disease of the appendix (DDA) is associated with a higher perforation rate, and Chia et al [ 30 ] have shown that a high SIRS score is useful in clinical decision making for surgery in DDA[ 30 ]. The total white blood cell count is a non-specific biochemical marker, and novel markers may improve the performance of scoring systems.…”
Section: Clinical Scoring Systemsmentioning
confidence: 99%
“…Imaging is integral not only to establish a diagnosis but also to rule out another diagnosis. These include right colonic diverticulitis[ 30 , 61 - 63 ], Yersinia enterocolitis[ 64 , 65 ], right-sided renal disease[ 66 ], mesenteric lymphadenitis[ 67 ] and Meckel’s Diverticulitis[ 68 , 69 ]. The meta-analysis investigating the role of MRI scan in pediatric AA reported that alternative diagnosis was present in about 20% of patients, most common being adnexal cyst and enteritis/colitis[ 61 ].…”
Section: Diagnostic Dilemmamentioning
confidence: 99%